Transformation and development of resource-based cities in China: A review and bibliometric analysis - Gu, Qifeng; Wu, Zhengyuan; Xie, Dongwei (Frontiers in Environmental Science, 2022)
With increasingly serious environmental and resource problems, resource-based cities have attracted unprecedented attention at home and abroad. In recent years, resource-based cities have become a hot research topic that has produced fruitful results. However, few articles have comprehensively and systematically reviewed the research on resource-based cities, which makes it difficult to carry out further research. This study introduces the influencing factors of the urban transformation of resource-based cities, the path of urban transformation and the evaluation index system of urban transformation in detail. At the same time, a total of 2,182 papers related to resource-based cities in CNKI and WOS from 2002 to 2022 were taken as the research object. CiteSpace software was used to conduct statistical analysis of publication date, journal of publication, institution, and highly cited literature. Using the co-occurrence network of literature keywords and the analysis of emergent words, the research status of resource-based cities at home and abroad is visually analyzed. It is found that Chinese universities attach the most importance to research on resource-based cities. Chinese language journals focus on urban transformation and economic transformation, while English language journals focus on sustainable development and the circular economy, which are quite different. The overall research content of Chinese journals is scattered, the co-occurrence ability of keywords is weak, and the duration of hot research topics is short. In contrast, the overall research trend of English language journals is more concentrated, the key words' emergence intensity is high, and the duration is long. This study aims to systematically sort out the theories and research related to resource-based city development in China and internationally, clarify the key issues of resource-based city research and the shortcomings of existing research, and put forward feasible suggestions for future research.